PENGARUH SUKU BUNGA DAN NILAI TUKAR RUPIAH TERHADAP INDEKS HARGA SAHAM GABUNGAN (IHSG) PERIODE 2015-2017 - Dini Arifian; Epi Pudin (The Asia Pacific Journal Of Management Studies, 2018)
This study aims to determine the movement of the composite stock price index influenced by interest rates and the exchange rate of the rupiah. The method used is a quantitative method, with descriptive statistics, with population data index, interest rates, and exchange rates for the period January 2015 - December 2017, with smapling saturated. by using secondary data, the analysis technique used is the prerequisite test analysis, and hypothesis testing. Based on the results of the partial t test analysis of interest rates shows tcount> t table (7.663 <1.693) means that interest rates have a significant effect on the CSPI, and for the exchange rate obtained tcount> t table (4,819> 1,639) means that the exchange rate has a significant effect on the CSPI, and based on f test simultaneously obtained the value of the results of fcount and ftabel, that fcount = 48.021> ftabel = 3.30 there is a significant influence between interest rates and exchange rates on the composite stock price index (CSPI), with a strong correlation coefficient. The conclusion is that interest rates and exchange rates have a significant negative effect on the composite stock price index (CSPI).